2020
DOI: 10.1155/2020/8361798
|View full text |Cite
|
Sign up to set email alerts
|

Role of Platelet-Rich Plasma in Spinal Fusion Surgery: Systematic Review and Meta-Analysis

Abstract: Background. Platelet-rich plasma (PRP) has been used very successfully in enhancing bone fusion in animal experiments. Also, the efficaciousness of PRP in other specialties of medicine such as dentistry, dermatology ophthalmology, and sports medicine is well documented. But the use of PRP to augment bone fusion after spinal surgery in humans is still controversial. We conducted a meta-analysis to determine the role of PRP in enhancing spinal fusion by fastening the rate of new bone formation and decreasing pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Through experimental and clinical research, we now have a better understanding of platelet and other cellular physiology. Furthermore, several high-quality systematic reviews, meta-analyses, and randomized controlled trials signify the effectiveness of PRP biotechnology in many medical fields, including dermatology [ 45 ], cardiac surgery [ 46 ], plastic surgery [ 47 ], orthopedic surgery [ 48 ], pain management [ 49 ], spinal disorders [ 50 ], and sports medicine [ 51 , 52 ].…”
Section: A Contemporary Prp Formulation: “Clinical Prp”mentioning
confidence: 99%
“…Through experimental and clinical research, we now have a better understanding of platelet and other cellular physiology. Furthermore, several high-quality systematic reviews, meta-analyses, and randomized controlled trials signify the effectiveness of PRP biotechnology in many medical fields, including dermatology [ 45 ], cardiac surgery [ 46 ], plastic surgery [ 47 ], orthopedic surgery [ 48 ], pain management [ 49 ], spinal disorders [ 50 ], and sports medicine [ 51 , 52 ].…”
Section: A Contemporary Prp Formulation: “Clinical Prp”mentioning
confidence: 99%
“…Finally, 3 meta-analyses were included in this systematic overview. 19 - 21 These overlapping meta-analyses were published in different journals in 2020 and the number of included studies ranged from 11 to 14 as shown in Table 1 . The publication years of the included studies in these meta-analyses ranged between 2003 and 2019 as shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, multiple meta-analyses have been published in this regard analyzing the effectiveness of PRP in enhancing spinal fusion. 19 - 21 However, these overlapping meta-analyses further added to the controversy due to their inconsistent results and conflicting conclusions because of the variability in the primary studies included for meta-analysis. Every meta-analysis suffered from a limited pooled sample size.…”
Section: Introductionmentioning
confidence: 99%
“…PRP is a concentrate of platelets and other growth factors, which have been implicated as a potent biomaterial in regenerative medicine. In the PRP, the presence of platelet-derived biomaterials (PDB) such as epidermal growth factor (EGF), vascular endothelial growth factor (VEGF), epithelial cell growth factor (EGR), hepatocyte growth factor (HGF), insulin-like growth factor (IGF), platelet-derived growth factor (PDGF), platelet-derived angiogenesis factor (PDAF), platelet factor-4 (PF-4), transforming growth factor (TGF), Il-1, IL-6, and TNF-α have been reported to initiate and participate in the progression of bone fusion and healing [ 215 , 216 ]. Recent pre-clinical and clinical studies have also implicated the potential of PRP in promoting bone fusion during lumbar infusion surgeries.…”
Section: Regenerative Therapeutic Approaches For Bone Grafting Andmentioning
confidence: 99%
“…However, a systemic review and meta-analysis concluded that PRP could not contribute significantly in bone fusion as well as pain relief [ 223 ]. Although PRP-containing growth factors possess the potential to induce bone formation and fusion, the lack of a continuous pattern limits reaching a clear consensus [ 215 ]. Consequently, combined strategies of PRP and MIS-TLIF need to be explored to establish its therapeutic potential.…”
Section: Regenerative Therapeutic Approaches For Bone Grafting Andmentioning
confidence: 99%